2016
DOI: 10.1007/978-3-319-27069-2_11
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Autism Spectrum Disorders

Abstract: In the last 30 years, twin studies have indicated a strong genetic contribution to Autism Spectrum Disorders (ASD). The heritability of ASD is estimated to be 50 %, mostly captured by still unknown common variants. In approximately 10 % of patients with ASD, especially those with intellectual disability, de novo copy number or single nucleotide variants affecting clinically relevant genes for ASD can be identified. Given the function of these genes, it was hypothesized that abnormal synaptic plasticity and fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 140 publications
(156 reference statements)
1
45
0
1
Order By: Relevance
“…Moreover, heritability studies have variably calculated ASD environmental risk factor influence at 7 to 35 % (Tick et al 2016), 5 to 44 % (Colvert et al 2015), 50 % (Sandin et al 2014), and 55 % (Hallmayer et al 2011). Huguet et al (2016) reviewed ASD findings and proposed a specific distribution of ASD risk factors: 49.8 % common inherited variants, 2.6 % rare inherited CNVs and SNVs, 6.6 % de novo SNVs, 2.9 % de novo CNVs, and 38.1 % environmental risk factors. Huguet et al (2016) considered the de novo SNVs and CNVs to be environmental and thus 52.4 % of ASD had genetic causes, and 47.6 % had environmental causes.…”
Section: Brain Validity Research Approach 5: Do Multiple Asd Genes DImentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, heritability studies have variably calculated ASD environmental risk factor influence at 7 to 35 % (Tick et al 2016), 5 to 44 % (Colvert et al 2015), 50 % (Sandin et al 2014), and 55 % (Hallmayer et al 2011). Huguet et al (2016) reviewed ASD findings and proposed a specific distribution of ASD risk factors: 49.8 % common inherited variants, 2.6 % rare inherited CNVs and SNVs, 6.6 % de novo SNVs, 2.9 % de novo CNVs, and 38.1 % environmental risk factors. Huguet et al (2016) considered the de novo SNVs and CNVs to be environmental and thus 52.4 % of ASD had genetic causes, and 47.6 % had environmental causes.…”
Section: Brain Validity Research Approach 5: Do Multiple Asd Genes DImentioning
confidence: 99%
“…Huguet et al (2016) reviewed ASD findings and proposed a specific distribution of ASD risk factors: 49.8 % common inherited variants, 2.6 % rare inherited CNVs and SNVs, 6.6 % de novo SNVs, 2.9 % de novo CNVs, and 38.1 % environmental risk factors. Huguet et al (2016) considered the de novo SNVs and CNVs to be environmental and thus 52.4 % of ASD had genetic causes, and 47.6 % had environmental causes. Most importantly, gene-environment interactions have been identified for ASD (LaSalle 2013;Jeste and Geschwind 2014;Volk et al 2014).…”
Section: Brain Validity Research Approach 5: Do Multiple Asd Genes DImentioning
confidence: 99%
“…These genes play a role in the 'evolvability' or capacity to adapt of the ape and human genome (Gualtieri, 2014). Whist the genetics of autism are complex, and over 1000 genes are involved in the risk of ASC (Liu et al, 2014), autism is found cross-culturally at similar rates (around 1-4% of the population) (Wakabayashi et al, 2007) and autism runs in families (52.4% heritability) (Baron-Cohen et al, 1998;Gaugler et al, 2014;Huguet et al, 2016). Whilst we often perceive autism spectrum conditions to be a 'disorder' they are best seen as an extreme of personality variation (Robinson et al, 2016).…”
Section: The Presence Of Individuals With Autism In Upper Palaeolithimentioning
confidence: 99%
“…Potentially thousands of SNPs that increase risk are scattered throughout the genome, which are thought to act additively (Klei et al, 2012). They also account for an estimated 95% of the heritable aspect of ASC (Gaugler et al, 2014;Huguet et al, 2016).…”
Section: The Presence Of Individuals With Autism In Upper Palaeolithimentioning
confidence: 99%
“…Development of therapeutics for autism spectrum disorder have been difficult, as there is no single underlying cause that can be easily targeted, and symptoms are widely variable patient to patient 89 .…”
Section: Future Directions and Studiesmentioning
confidence: 99%